PO-43 - Differential coagulation factor expression in neuroendocrine prostate cancer (PC), metastatic castrate-resistant PC, and localized prostatic adenocarcinoma. Issue 140 (April 2016) - Choe, H.; Sboner, A.; Beltran, H.; Nanus, D.; Tagawa, S.T.
Abstract : Introduction: Neuroendocrine prostate cancer (NEPC) is an aggressive late-stage variant of PC that is often androgen-receptor negative. Most clinicians believe the VTE rate with NEPC is higher than with standard metastatic castration-resistant PC (mCRPC), but NEPC tends to present with bulkier visceral disease and include platinum chemotherapy unlike standard PC. In many solid tumors, a more aggressive phenotype correlates with increased VTE risk and elevated expression of coagulation factors. We previously reported on the differential expression of thrombin and tissue factor (TF) in NEPC versus localized PC and benign prostate tissue with a small NEPC cohort (N = 7), which showed overexpression of prothrombin and reduced expression of TF in NEPC. Aim: To compare the expression of coagulation factors of NEPC vs mCRPC (and localized PC control) in an expanded datase. Materials and Methods: Fresh frozen tissue biopsies were collected and separated into three cohorts based on pathology: localized PC (N = 68), standard mCRPC (N = 32), and NEPC (N = 21). RNA was isolated and next generation paired-end mRNA sequencing was performed on Illumina Sequencers. F2 Prothrombin (F2), tissue factor (F3), carboxypeptidase (CPB2), fibrinogen (FGG, FGA), PAR-1 (F2R), and PAR-2 (F2RL1) were compared by Wilcoxon tests. Results: Prothrombin had significantly higher expression in NEPC versus standard mCRPC (p < 0.001). NEPC trended towards higher expression of CPB2 (p = 0.1) and lower expression of F3 (p = 0.23) and F2RL1 (p = 0.14) compared to mCRPC. Compared to localized PC, both types of advanced disease (NEPC and mCRPC) overexpressed F2, FGA, FGB, and CPB2 (p < 0.001) and had decreased expression of F3 and F2RL1 (p < 0.001). Conclusions: Prothrombin is reliably overexpressed in NEPC vs mCRPC and localized PC. Advanced disease (regardless of subtype) is associated with significantly higher expression of prothrombin, fibrinogen, and carboxypeptidase and lower expression of TF and PAR-2. It is possible that there may be PC-specific differences with aggressive disease associated with the thrombin axis vs the more common TF/PAR2 axis commonly seen in other advanced solid tumors. Further research is required to understand these differences in biology and resulting thrombotic and hemostatic outcomes.